Uso de paclobutrazol no tratamento de sementes como inibidor de estiolamento de mudas de tomateiro - Rezende, Édila Maria de (2016)
Tomato planting for in natura consumption is performed by means of seeding in trays with posterior transplanting of the seedlings. In this production system, the highest cause for seedling loss is the excessive growth of the stem (estiolation). Some inhibitors, such as paclobutrazol, have been used to reduce this growth and minimize such effect. Thus, in the present work, we aimed at evaluating the effect of dosses of paclobutrazol, with and without the association of polymers, over the physiological quality of the seeds and over the control of the estiolation. Seeds of two tomato cultivars, Ozone and Paronset, were treated with four concentrations of paclobutrazol (0, 0.004, 0.008 and 0.016 mL ia.10 g seeds-1), combined with three fixatives (water, average permeability polymer – P1, and high permeability polymer – P2). The experiment was conducted partially in laboratory, with the evaluation of the germination speed index, percentage of germination and cold test; partially in greenhouse, evaluating stem diameter, shoot and root length, total, shoot and root dry matter and leaf area; and in the field, evaluating the height of the first and second inflorescences, stem diameter at the base of the plant and at the base of the first inflorescence, and mean growth rate. After five months of seed storage, the same physiological analysis were conducted in laboratory. With the results, we verified that the increase in the dose of PBZ reduced the percentage of germination, germination speed index, plant emergence and emergence speed index for both cultivars. There was difference in the behavior of both cultivars concerning the action of PBZ. For cultivar Ozone, with the increase of PBZ, the length of the shoot and leaf area decrease; the hypocotyl diameter/shoot length relation increases; field plant growth decreases until the second week post-transplanting; and the different doses of PBZ do not alter the height of the first inflorescence. For cultivar Paronset, the doses of PBZ decrease the height of the first inflorescence and the diameter at the base of the stem. The synthetic polymers in the used dose are efficient in the fixation of PBZ to the seed tegument, but do not decrease PBZ absorption speed by the seeds during the germination test.